Perbandingan Penerapan Metode Peer Group Dengan Metode Ceramah Dalam Pendidikan Kesehatan Terhadap Kesadaran Perilaku Sadari Terhadap Remaja Putri Di Smpn 1 Talaga Kabupaten Majalengka - Oktaviani, Pearly Otis Putri; Astuti, Ani (Indonesia Berdaya, 2024)
Breast cancer is an urgent global health problem. It is estimated that more than 2 million new cases of breast cancer are diagnosed each year worldwide, making breast cancer the most common type of cancer in women. The aim of this research is to determine the comparison of the application of the peer group method with the lecture method in health education on awareness of BSE behavior in young women at SMPN 1 Talaga. This research used a pre-experimental method with a one group pre-test post-test design, which was carried out as a benchmark for the intervention. Post-test activities were carried out on the same day to minimize bias. The population in the study was 103 young women who were grade 9 students at SMPN 1 Talaga Majalengka. Based on the results of statistical tests using the paired sample t-test, with the help of SPSS version 21 with a significance level of α = 0.05, the result was p = 0.002, which means p 0.05, namely H1 is accepted, which means there is a difference between the application of the peer group method. using the lecture method in health education towards awareness of BSE behavior in young women at SMPN 1 Talaga. Health workers are expected to be able to adopt and apply peer group methods in health education in the community, especially among teenagers.